Imago Mundi: a salvação do mundo na poesia de Adélia Prado - Souza, Ewerton Menezes Fernandes de (2015)
This dissertation proposes to analyze poems comprehending Adélia Prado work, since her first book Bagagem, published in 1976, to her last work, Miserere, released on 2013. It is discussed how adelian poetry lays ahead both values in the world and modern poetry, trying to find which are the fundamental elements for the author s choice which allow to notice the presence of a poetic project reigning the development of her work. For such, we look to answer the following questions: how is done the dialogue with modernity conditioned by Christian values, which the author s poetry adheres? Which poetic project results from the stress between modernity values to Christian values present in adelian poetry? Which are the elements allowing the dialogue from Adelia Prado s work to her time, generating affinities and distinctions? It is thought, as an answer for such questions, the hypothesis that adelian poetry is built as an interpellation of the modernity values resulting in a poetic project trying to save the individual and the image of the world linked to the first, subscribing them within the poem. For such, Christian beliefs about incarnation and resurrection, responsible to make viable the subscription of the man and the world in the texture of the poetic text, thought as a body and territory of imago mundi, which is desired to preserve. With such intent, we have searched in the theoretical works by authors such as George Steiner and Octavio Paz, regarding to questions about modernity, to which, there is the addition of works by Mircea Eliade, Michael Henry, Tzvetan Todorov and Miguel Unamuno, regarding to poetry and religion. As a methodological strategy along the four chapters, we placed the quoted authors in a dialogue with the analysis of the corpus. On the closing remarks, reaffirming the suggested hypothesis, noticing it as a way in which the poet has to answer to the problems of modernity, which the work establishes a stressed relation of pertaining and refusal